Linear programming and network flows - Bazaraa, M. S.; Jarvis, John J.; Sherali, Hanif D. , 1952- (John Wiley & Sons, 2010)
The only book to treat both linear programming techniques and network flows under one cover, this book has been conpletely updated with the latest developments on the topic. This new edition continues to successfully emphasize modeling concepts, the design and analysis of algorithms, and implementation strategies for problem in a variety of fields, including industrial engineering, management science, operations research, computer science, and mathematics